DOI : 10.5958/j.0976-478X.5.2.019 Inventory Management in KECL (Keltron Electro Ceramics Limited) - A. Dharmaraj (Journal of Commerce and Management Thought, 2014)
Inventory is most important assets that most business possesses, because the turnover of inventory implicates one of the primary sources of gaining revenue and subsequent earning for the company’s shareholders. Primarily inventory management about specifying the size and placement of stocked goods. The Indian Electronics is one of the fastest growing sectors of the Indian Industry. Determination of optimal inventory procedure for the procurement of the stocks of commodities to meet future demands. So present study is made to know the inventory in Keltron Electro Ceramics Limited, Kuttipuram – Kerala. Ratio analysis, correlation and ABC analysis are used to analysis the data. It is concluded that better co-ordination among purchases, stores, production, marketing and finance departments will help in achieving efficiency in inventory management.